Determination of frost resistance for sorts of winter wheat and barley based on the insight of membranes - Bunduk, Yu.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of the research dedicated to the indication of the optimal factors of the relative issue of electrolytes from the germs of the winter wheat and barley for the evaluation of their frost-resistance.